The Evaluation of Maqāṣid Asy-Syarī’ah on Discourses of the Islamic Family Law - Taufiqurohman, Taufiqurohman; Fauziah, Nelli (El-Usrah: Jurnal Hukum Keluarga, 2023)
The concept of maqāṣid syarī‘ah and its relationship to family law is an intriguing topic for academic inquiries and discussion. The maqāṣid syarī‘ah is a concept that defines a goal of the Islamic law for the betterment of life in this world and the hereafter. This objective is achieved in human existence by safeguarding religion, soul, reason, progeny, and property. The term al-aḥwāl al-syakhṣiyyah, which refers to kinship relations, can be considered a substitute for the term munākaḥāt, which is commonly used in classical fiqh texts. The numerous issues that intersect with the concept of family law must be viewed through the lens of sharia objectives. How then does the Shari'ah respond? This article attempts to analyze it using a literature review and the maqāṣid syarī‘ah analysis instrument. Based on al-‘ādat from al-Syāṭibī, the understanding of al-aḥwāl al-syakhṣiyyah should be based on the interpretation of the meaning of the texts of the Qur'an and hadith, so that religious texts related to al-awl al-syakhiyyah are not positioned as a form of legal-formal rule, but rather as a search for the meaning contained in religious arguments in the Islamic law